Parent's Just Don't Understand: Parental Support, Religion and Depressive Symptoms among Same-Race and Interracial Relationships - Henderson, Andrea K. (Religions, 2019)
Research finds that individuals in interracial relationships have poorer mental health than those in same-race relationships. Family support, or lack thereof, may play an important role in explaining the psychological risks for such individuals. Growing attention has focused on the complex interplay between religion, health, and family life, particularly the stress-buffering role of religious involvement. However, little attention has been given to the possible mitigating effects of religion in the face of limited family support among same-race and interracial couples. Using data from the National Longitudinal Study of Adolescent to Adult Health (Add Health), this study addresses two important questions: (1) Is weak family support associated with depressive symptoms among individuals in same-race and interracial relationships?; and (2) Does religious involvement buffer the association between weak family support and depressive symptoms for individuals engaged in these romantic ties? Results suggest that weak parental support is associated with depressive symptoms for individuals in both same-race and interracial relationships, however we find limited support of religion protecting against weak parental support for individuals in interracial unions. The results highlight the complex interplay between religion, health, and family in contemporary American life.